2022
DOI: 10.3389/fpls.2022.1023837
|View full text |Cite
|
Sign up to set email alerts
|

The wilt pathogen induces different variations of root-associated microbiomes of plant

Abstract: Root-associated compartments, including the rhizosphere, rhizoplane, and endosphere, live with diverse microbial communities which profoundly affect plant growth and health. However, a systematic understanding of the microbiome assembly across the rhizosphere, rhizoplane, and endosphere under pathogen invasion remains elusive. Using 16S high-throughput sequencing, we studied how bacterial wilt disease affected the variation and assembly of the three continuous root-associated microbiomes of tobacco. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 52 publications
3
15
1
Order By: Relevance
“…This indicated that T2 was more complex, with abundant interactions in a highly connected microbial community, which might also be explained by the rainfall peak at T2 that has provided great growth opportunity for microbes to multiply and make connections as mentioned above. A similar phenomenon of relatively higher connections was also observed in the wilt diseased rhizoplane of tobacco (Tao et al, 2022) . The percentage of positive correlation follow largely a downtrend from T1 (57.4%) to T3 (53.6%), indicating the decrease of cooperative relation.…”
Section: Molecular Ecological Network Of Phyllospheric Bacterial Comm...supporting
confidence: 72%
“…This indicated that T2 was more complex, with abundant interactions in a highly connected microbial community, which might also be explained by the rainfall peak at T2 that has provided great growth opportunity for microbes to multiply and make connections as mentioned above. A similar phenomenon of relatively higher connections was also observed in the wilt diseased rhizoplane of tobacco (Tao et al, 2022) . The percentage of positive correlation follow largely a downtrend from T1 (57.4%) to T3 (53.6%), indicating the decrease of cooperative relation.…”
Section: Molecular Ecological Network Of Phyllospheric Bacterial Comm...supporting
confidence: 72%
“…For example, Xiong, He, et al (2021); Xiong, Zhu, et al (2021) found that soil is the main source of microorganisms colonizing the root compartments, which are then filtered and enriched in the leaf compartments, along the soil–plant continuum. However, recent studies suggest that the major sources of microbiomes in specific compartments may be altered by disturbances (Dove et al, 2021; Sun et al, 2022) or pathogen infections (Dastogeer et al, 2022; Tao et al, 2022). Therefore, it is important to investigate whether mowing can shift the sources of leaf and root microbiomes and elucidate the mechanisms underlying the recruitment of microbes by plant compartments under mowing (Sun et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(2020) revealed that the rhizosphere and endophytic compartments of infected tobacco were more complex compared to those of healthy tobacco. Similarly, a higher level of connections was also observed in the wilt-diseased rhizoplane of tobacco compared to healthy samples ( Ahmed et al., 2022 ; Tao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 73%